A study of serum concentrations and dermal levels of NGF in atopic dermatitis and healthy subjects - Papoiu, Alexandru; Wang, Hui; Nattkemper, Leigh; Tey, Hong Liang; Ishiuji, Yozo; Chan, Yiong-Huak; Schmelz, Martin; Yosipovitch, Gil (Neuropeptides, 2011)
Nerve growth factor (NGF) was reported to be increased in the serum and skin of atopic dermatitis (AD) patients, to the extent that serum nerve growth factor levels were proposed to serve as a marker of disease severity. We studied NGF levels in the serum and dermis using skin microdialysis and attempted to correlate them with disease severity. We also examined if potential differences between morning and evening levels of NGF can explain the phenomenon of nocturnal itch. In addition, neurogenic inflammation and itch were induced using histamine iontophoresis in lesional and non-lesional skin and the effect of experimental itch on dermal NGF concentration was examined. We found that systemic (serum) and eczematous skin levels of NGF in AD are significantly lower in comparison to healthy controls. Serum NGF decreases from morning to late afternoon in both groups. Interestingly, serum NGF levels were correlated to disease severity in the morning in AD, although the NGF concentration in AD were significantly lower than in the healthy group. The local itch and neurogenic inflammation induction via experimental histamine reduced local NGF levels in the eczema and non-lesional skin in atopics, but not in the healthy controls, where it was slightly increased. The higher the clinical severity of the eczema, a significantly less pronounced effect of neurogenic inflammation on the local levels of NGF was found. The availability of measurable NGF might be reduced by a higher expression of NGF receptors. The fluctuations of NGF levels during the day suggest a complex modulation of this neurotrophin, potentially linked to stress or to an altered neurophysiological mechanism.